2021
DOI: 10.3389/fpls.2021.740755
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Four Comparative-Omics Reveals the Mechanism of the Terpenoid Biosynthesis in Two Different Overwintering Cryptomeria fortunei Phenotypes

Abstract: Chinese cedar (Cryptomeria fortunei) is a tree species with important ornamental, medicinal, and economic value. Terpenoids extracted from the essential oil of C. fortunei needles have been considered valuable ingredients in the pharmaceutical and cosmetic industries. However, the possible gene regulation mechanisms that limit terpenoid biosynthesis in this genus are poorly understood. Here, we adopted integrated metabolome analysis, transcriptome, small-RNA (sRNA), and degradome sequencing to analyze the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Similarly, another study of potato seedling miRNAs revealed that the novel miRNA stu-novel-miR5125 targeted beta-carotene 3-hydroxylase, which could be upregulated by low-temperature stress [44]. Furthermore, a miRNA regulatory network from Cryptomeria fortunei, a medicinal plant from China, indicated that several miRNAs, including pde-miR159, mdm-miR396a, and hbr-miR6173 were related to the carotenoid biosynthesis [45].…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, another study of potato seedling miRNAs revealed that the novel miRNA stu-novel-miR5125 targeted beta-carotene 3-hydroxylase, which could be upregulated by low-temperature stress [44]. Furthermore, a miRNA regulatory network from Cryptomeria fortunei, a medicinal plant from China, indicated that several miRNAs, including pde-miR159, mdm-miR396a, and hbr-miR6173 were related to the carotenoid biosynthesis [45].…”
Section: Discussionmentioning
confidence: 97%
“…Subsequently, terpenoids are generated via the catalytic actions of various terpene synthases [3][4][5][6]. The monoterpenoids are mainly generated through the MEP pathway [7]. Notably, 1-hydroxy-2-methyl-2-(E)-butenyl-4-diphosphate reductase (HDR) serves as the catalytic enzyme in the last step of the MEP pathway, which precisely regulates the generation of the mixture of IPP and DMAPP [8][9][10].…”
Section: Introductionmentioning
confidence: 99%